2020
DOI: 10.6023/a20060252
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay Applications of Aptamer-Functionalized Rare Earth Nanomaterials

Abstract: The levels of some biomolecules and ions in the body are usually related to the structural and functional changes of cells, tissues, organs, etc., which directly affect the prevention, diagnosis, and treatment of diseases. Therefore, in vivo bioassays of these substances are of great significance in medical and healthcare fields. The nano fluorescent probes consisted of rare earth nano materials have advantages of high sensitivity, simplicity, efficiency, and strong anti-interference ability, thus showing grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Based on the above UV–Vis and IR spectra and the possible reaction mechanism between styrene and ozone, it can be confirmed that formaldehyde, formic acid, benzene, phenol, benzaldehyde, and benzoic acid are the main constituents of styrene SOA particles. This is consistent with the product information detected in the styrene ozonolysis experiments conducted by Chiappini et al, [ 9 ] Jia et al, [ 11 ] and Na et al [ 12 ] Compared with the previous styrene chamber experiments, [ 8–12 ] VUV‐PIMS is used to on‐line characterize the components of SOA particles in this study. By controlling the photon flux, VUV‐PIMS on‐line measurement technology based on synchrotron radiation photoionization can minimize the possibility of dissociation of tested organic molecules, reduce the generation of fragment ions, and obtain the molecular ion peak of the component.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Based on the above UV–Vis and IR spectra and the possible reaction mechanism between styrene and ozone, it can be confirmed that formaldehyde, formic acid, benzene, phenol, benzaldehyde, and benzoic acid are the main constituents of styrene SOA particles. This is consistent with the product information detected in the styrene ozonolysis experiments conducted by Chiappini et al, [ 9 ] Jia et al, [ 11 ] and Na et al [ 12 ] Compared with the previous styrene chamber experiments, [ 8–12 ] VUV‐PIMS is used to on‐line characterize the components of SOA particles in this study. By controlling the photon flux, VUV‐PIMS on‐line measurement technology based on synchrotron radiation photoionization can minimize the possibility of dissociation of tested organic molecules, reduce the generation of fragment ions, and obtain the molecular ion peak of the component.…”
Section: Resultssupporting
confidence: 90%
“…In the infrared spectrum, 3,667 and 1,657 cm −1 correspond to the stretching vibration peaks of OH and CO, which can confirm the existence of carboxylic acids in extraction solutions. Also, peak at 1,249 cm −1 is the stretching vibration peak of CO in phenolic substances, [ 11,64 ] which further authenticates that the major constituents of styrene SOA particles are phenolic and carbonyl compounds.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Lanthanide metal–organic frameworks (Ln-MOFs) constructed by lanthanide nodes and organic linkers via coordination bonds are promising sensing materials for not only their permanent porosities and structural tunabilities , but also excellent photoluminescence based on an “antenna effect” with rapid and efficient sensing performance because the photoluminescence of Ln-MOFs can be fine-tuned by the host–guest interaction through rational structure and energy-level matching. To date, well-designed luminescent Ln-MOFs have successfully been studied for the detection of gases, cations, anions, volatile organic compounds and persistent organic pollutants, , chiral molecules, biomakers, biomolecules, and so on. However, to the best of our knowledge, the application of Ln-MOFs for the detection of PA or its biomarker has not been reported.…”
Section: Introductionmentioning
confidence: 99%